Apus apus subsp. apus ... - Boano, Giovanni; Belemsobgo, Urbain; Silvano, Fabrizio; Hema, Emmanuel M.; Belemsobgo, Aristide; Dimobe, Kangbéni; Pavia, Marco (Zenodo, 2022)
Apus apus apus (Linnaeus, 1758) LITERATURE. — Green & Sayer (1979); Thonnérieux et al. (1989); Dowsett (1993); Balanca & de Visscher (1997); Mauvais (1998); Borrow & Demey (2001, 2014); Portier (2002c); Balanca et al. (2007); Sinclair & Ryan (2010); Dowsett et al. (2013). FIELD DATA. — eBird; GBIF; WABD. STATUS. — Palaearctic migrant. ... : Published as part of Boano, Giovanni, Belemsobgo, Urbain, Silvano, Fabrizio, Hema, Emmanuel M., Belemsobgo, Aristide, Dimobe, Kangbéni & Pavia, Marco, 2022, An annotated checklist of the birds of Burkina Faso, pp. 27-107 in Zoosystema 44 (2) on page 39, DOI: 10.5252/zoosystema2022v44a2, http://zenodo.org/record/5999691 ...